Brief provider communication skills training fails to impact patient hypertension outcomes. Issue 2 (February 2015) - Manze, Meredith G.; Orner, Michelle B.; Glickman, Mark; Pbert, Lori; Berlowitz, Dan; Kressin, Nancy R.
Highlights: We test a provider training to improve patient hypertension outcomes. Training to improve communication skills related to patient-centeredness. The intervention did not improve counseling, adherence or blood pressure outcomes. It may have been too brief and lacked sufficient practice level changes. Abstract: Objectives: Hypertension remains a prevalent risk factor for cardiovascular disease, and improved medication adherence leads to better blood pressure (BP) control. We sought to improve medication adherence and hypertension outcomes among patients with uncontrolled BP through communication skills training targeting providers. Methods: We conducted a randomized controlled trial to assess the effects of a communication skills intervention for primary care doctors compared to usual care controls, on the outcomes of BP (systolic, diastolic), patient self-reported medication adherence, and provider counseling, assessed at baseline and post-intervention. We enrolled 379 patients with uncontrolled BP; 203 (54%) with follow-up data comprised our final sample. We performed random effects least squares regression analyses to examine whether the provider training improved outcomes, using clinics as the unit of randomization. Results: In neither unadjusted nor multivariate analyses were significant differences in change detected from baseline to follow-up in provider counseling, medication adherence or BP, for the intervention versus control groups. Conclusion: The intervention did not improve the outcomes; it may have been too brief and lacked sufficient practice level changes to impact counseling, adherence or BP. Practice Implications: Future intervention efforts may require more extensive provider training, along with broader systematic changes, to improve patient outcomes.